2014
DOI: 10.1186/1472-6963-14-218
|View full text |Cite
|
Sign up to set email alerts
|

Functions of behavior change interventions when implementing multi-professional teamwork at an emergency department: a comparative case study

Abstract: BackgroundWhile there is strong support for the benefits of working in multi-professional teams in health care, the implementation of multi-professional teamwork is reported to be complex and challenging. Implementation strategies combining multiple behavior change interventions are recommended, but the understanding of how and why the behavior change interventions influence staff behavior is limited. There is a lack of studies focusing on the functions of different behavior change interventions and the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…Even if it were possible to find stable organizations for an intervention study, the results from such an intervention would likely have limited generalizability (i.e., external validity) (Griffiths, A., 1999) as organizations, not least in healthcare and residential care for older people, face continuous changes. Therefore, it could be argued that instead of trying to avoid concurrent changes, there is a need for researchers to be aware of how concurrent changes may influence outcomes and to integrate concurrent changes in the planned intervention and in evaluation frameworks (Frykman, Hasson, Athlin, & von Thiele Schwarz, 2014;Nielsen, Taris, et al, 2010). By planning for potential changes in advance and monitoring the discrete context during the intervention, potential threats of concurrent changes that may hinder intervention implementation can be detected and activities to avoid them can be undertaken (Frykman et al, 2014).…”
Section: Changes Occurring During the Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if it were possible to find stable organizations for an intervention study, the results from such an intervention would likely have limited generalizability (i.e., external validity) (Griffiths, A., 1999) as organizations, not least in healthcare and residential care for older people, face continuous changes. Therefore, it could be argued that instead of trying to avoid concurrent changes, there is a need for researchers to be aware of how concurrent changes may influence outcomes and to integrate concurrent changes in the planned intervention and in evaluation frameworks (Frykman, Hasson, Athlin, & von Thiele Schwarz, 2014;Nielsen, Taris, et al, 2010). By planning for potential changes in advance and monitoring the discrete context during the intervention, potential threats of concurrent changes that may hinder intervention implementation can be detected and activities to avoid them can be undertaken (Frykman et al, 2014).…”
Section: Changes Occurring During the Interventionmentioning
confidence: 99%
“…Therefore, it could be argued that instead of trying to avoid concurrent changes, there is a need for researchers to be aware of how concurrent changes may influence outcomes and to integrate concurrent changes in the planned intervention and in evaluation frameworks (Frykman, Hasson, Athlin, & von Thiele Schwarz, 2014;Nielsen, Taris, et al, 2010). By planning for potential changes in advance and monitoring the discrete context during the intervention, potential threats of concurrent changes that may hinder intervention implementation can be detected and activities to avoid them can be undertaken (Frykman et al, 2014). Actions that could be used to avoid this are likely to differ depending on the type of change (e.g., changes in management, concurrent projects, or restructuring or downsizing) and should be investigated in further studies.…”
Section: Changes Occurring During the Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies utilized a comparative case study design incorporating a combination of interviews, Numbering is used to denote match variables across models; not all models tested the same sets of variables focus groups, observation, and document review, whereas two studies employed a cross-sectional descriptive design. Although three of the five studies reported their analytic design was informed by a theory or previously established model, only one study included an interview guide in which items were explicitly linked to theory [19]. All qualitative studies explored relations between multiple ecological levels, drawing connections between intra and interpersonal behavioral constructs and organization or system level change.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…Thus far, the support provided by line managers during implementations of participatory organizational interventions has mainly been examined after the intervention, on the same measurement occasion as intervention outcomes (Nielsen & Randall, ), thus offering limited information on temporal aspects. One exception is a study investigating what affected the intervention process of a teamwork intervention (Frykman, Hasson, Athlin, & Thiele Schwarz, ). The study showed that line managers had a central motivating role during the active intervention phase, whereas their support was less important once teamwork had become an established daily practice, because by that time, task‐related feedback had become a more important motivator.…”
Section: Perceived Line Managers' Support Of Organizational Interventmentioning
confidence: 99%